The Influence of Hydrogen Concentration on the Hazards Associated with the Use of Coke Oven Gas - Mateusz Klejnowski; Katarzyna Stolecka-Antczak (Energies)
Coke oven gas (COG), as a by-product of the coking process and a mixture with a high hydrogen content, is an important potential component of the sustainable economy of the coking industry. Ongoing studies and analyses are looking at many opportunities for the utilization of coke oven gas, including for the production of hydrogen, methanol or other chemicals. However, it is important not to forget that all processes for the utilization of this gas may pose a potential hazard to humans and the environment. This is due to the physicochemical properties of COG and the content of flammable gases such as hydrogen, methane or carbon monoxide in its composition. Potential hazardous events are also related to the content of toxic substances in the composition of coke oven gas. The publication focuses on the occurrence of a fire or explosion as a result of the uncontrolled release of purified coke oven gas from the installation. The potential hazard zones associated with the occurrence of these phenomena are presented concerning different levels of hydrogen concentration in coke oven gas and the influence of selected factors on the range of these zones. Zones related to human deaths due to fire of coke oven gas reached a maximum range of about 130 m from the site of the failure, depending on the gas composition, level of damage and parameters of the installation. Zones related to human deaths due to the explosion of the coke oven gas did not occur. The zone related to the injury of humans as a result of the COG explosion reached a maximum range of about 12 m.